Le Libro de los exemplos por ABC, recueil d’exempla du xve siècle - Bernard Darbord (Perspectives Médiévales)
This article deals with a collection of spanish exempla : the Libro de los exemplos por ABC written by Clemente Sánchez de Vercial (XVth century). Its sources and some of its main themes (friendship and charity) are analysed through various excerpts.